Oligosaccharides isolated from Rehmannia glutinosa protect LPS-induced intestinal inflammation and barrier injury in mice - Li, Xiao; Gui, Rong; Wang, Xuefang; Ning, Erjuan; Zhang, Lixian; Fan, Yi; Chen, Ling; Yu, Liqin; Zhu, Jie; Li, Zhining; Wei, Lei; Wang, Wei; et al. (Frontiers in Nutrition, 2023)
Rehmannia glutinosa is not only a traditional Chinese medicine, but also has a long history of consumption in China. We identified the composition and relative content of oligosaccharides isolated from Rehmannia glutinosa, and explored the protective effect of Rehmannia glutinosa oligosaccharide (RGO) on intestinal inflammation and barrier damage induced by lipopolysaccharide (LPS) in mice.The results showed that RGO was mainly composed of stachyose, raffinose and verbascose, the relative content of which is 81.02%, 5. 19% and 4.85% respectively, and the total amount of oligosaccharides was 91.06%. RGO significantly increased the weight (P<0.01), pancreatic index (P<0.01), thymus index (P<0.01), and colon length (P<0.01) of mice compared with the model group. Moreover, it also improved the intestinal tissue structure and increased the expression of intestinal barrier-related junction proteins occludens- 1 (ZO-1) and Occludin (P<0.01). The contents of IL-6, IL- 17, IL- 1β, and TNF-α in the intestinal tissues of mice were significantly reduced (P<0.01). Additionally, the activities of SOD, GSH- Px, and CAT were elevated (P<0.01). In contrast, the malondialdehyde (MDA) content decreased (P<0.01). Trypsin and pancreatic lipase activities in the ileum enhanced (P<0.01), and the short-chain fatty acids (SCFAs) contents such as acetic acid, propionic acid, and butyric acid in the colon increased (P<0.01). The study on intestinal flora revealed that RGO could enhance the abundance of intestinal flora and improve the flora structure. After RGO intervention, the relative abundance of Firmicutes, Lactobacillus, and Akkermania bacteria in the intestinal tract of mice increased (P<0.01) compared with the model group, while that of Actinomycetes decreased (P<0.01). The intestinal microbiota structure changed to the case, with probiotics playing a dominant role. The correlation analysis indicated that Lactobacillus and Akkermania bacteria in the intestinal tract of mice were positively associated with SCFAs, Occludin, ZO-1, pancreatic amylase, SOD, and CAT activities. Moreover, they were negatively correlated with inflammatory factors IL- 6, IL- 17, IL- 1β, and TNF-α . It is suggested that RGO can decrease LPS-induced intestinal inflammation and intestinal barrier injury in mice and protect their intestinal function. RGO can ameliorate intestinal inflammation and maintain the intestinal barrier by regulating intestinal flora.